Ultra-Low Loss Graphene Plasmonic Waveguide for Chip-Scale Terahertz Communication - Lei Sun (IEEE Photonics Journal, 2021)
Field-programmable photonic array-based chips will be key components in realizing high-performance THz communication in the future. However, the optical diffraction limit prohibits their integration in chip-level sizes. Although plasmonic waveguides combined with graphene are able to possess mode transmission at THz wavelengths, their operational problems such as complex device structures or high transmission losses still cannot be addressed effectively. In this paper, by relying on a mechanism of THz surface plasmon mode of graphene and an energy distribution mechanism of the refractive index difference region, a novel hybrid graphene plasmonic waveguide is proposed, whose core design part is a simple gap-slot region. This waveguide's transmission distance is one order of magnitude longer than that of the conventional waveguide while retaining the benefit high energy confinement, under appropriate parameters. Hence the proposed waveguide can be an efficient candidate component of field-programmable photonic arrays for THz communication.